Pengaruh Precooling Dan Coating Terhadap Chilling Injury Buah Nanas ‘Queen’ (Ananas comosus L.) - Prabasari, Indira; Utama, Nafi A; Lestari, Mutiara I; Djaafar, Titiek F (Universitas Pattimura, 2024)
Pineapple (Ananas comosus L.) ‘Queen’ is very sensitive to chilling injury when stored at low temperatures. Symptoms of chilling injury are characterized by the appearance of a brown color on the fruit's flesh (blackheart, black spot, internal browning). Post-harvest treatments such as coating and precooling can prevent chilling injury. The research aimed to determine the effect of coating using 2% chitosan and precooling at 18°C before coating on the chilling injury of pineapple ‘Queen'. The research was carried out using experimental methods and arranged in a completely randomized design with six treatment levels, namely (P1) control, (P2) 1 day precooling without coating, (P3) 2 days precooling without coating, (P4) coating without precooling, (P5) coating preceded by one day of precooling, and (P6) coating preceded by two days of precooling. Parameter analysis includes firmness, total soluble solids, reducing sugars, total phenolic compounds, and percentage of chilling injury during 24 days of storage. Organoleptic tests were also carried out to see the effect of treatment on the taste and texture of 'Queen' pineapple. The results showed that pineapple fruit treated with precooling for one day without coating (P2) was the best treatment for preventing chilling injury during 24 days of storage.